Histamine H3 Receptor Antagonist Enhances Neurogenesis and Improves Chronic Cerebral Hypoperfusion-Induced Cognitive Impairments - Wang, Na; Ma, Jing; Liu, Jing; Wang, Jiangong; Liu, Cuilan; Wang, Hua; Liu, Yong; Yan, Haijing; Jiang, Shujun (Frontiers in Pharmacology, 2020)
Chronic cerebral hypoperfusion (CCH) is a neurodegenerative disease, which induces cognitive impairments in the central nervous system (CNS). Histamine H3 receptor (H3R) is an auto-receptor involved in the modulation of neurogenesis and synaptic plasticity in the CNS. However, the role of H3R in CCH-induced injury and the related mechanisms remain to be clarified. Here, we found that thioperamide (THIO), a H3R antagonist, promotes the proliferation of NE-4C stem cells under either normal or oxygen-glucose deprivation (OGD) condition in vitro. Thioperamide promotes the phosphorylation of cAMP-response element binding (CREB), and thereby up-regulates the expression and release of brain-derived neurotrophic factor (BDNF). However, H89, an inhibitor of protein kinase A (PKA)/CREB, reverses the effects of thioperamide on either BDNF expression and release or cell proliferation in NE-4C stem cells. Moreover, thioperamide has protective effects on OGD-induced impairment of cell viability and neuronal morphology in primary neurons in vitro. Furthermore, thioperamide enhanced neurogenesis in the dentate gyrus (DG) and subventricular zone (SVZ) regions in vivo, and ameliorated CCH-induced cognitive impairments. Taken together, these findings showed that thioperamide protects primary neurons against OGD-induced injury and promotes the proliferation of neural stem cells in DG and SVZ regions through CREB/BDNF pathways, thereby improving cognitive deficit.